A New Caged‐Glutamine Derivative as a Tool To Control the Assembly of Glutamine‐Containing Amyloidogenic Peptides. (25th November 2016) - Awad, Loay; Jejelava, Nino; Burai, Ritwik; Lashuel, Hilal A.
Abstract: We present the design, synthesis, and characterization of a novel photocaged glutamine derivative (modified on the side chain of glutamine), and describe its use in enhancing peptide stability and solubility. Our results demonstrate that this approach can be used to develop molecular switches to control the folding and β‐sheet formation of amyloidogenic peptides. Abstract : Caged amyloids : A photocaged glutamine derivative has been developed by modifying the side chain of glutamine. It enhances peptide solubility and can be used as a molecular switch to control the folding and formation of β‐sheet structures of glutamine‐containing amyloidogenic peptides, as demonstrated by TEM.